2013
DOI: 10.1002/adsc.201200352
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Intramolecular Chloroamination of Unfunctionalized Olefins

Abstract: A new method for the intramolecular chloroamination of unfunctionalized olefins is reported. The reactions were carried out at room temperature for 3 h using hydrated copper(II) chloride as both promoter and chlorine source, and the corresponding vincinal haloamines were obtained in good isolated yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…When an aryl aldehyde bears an electron‐donating group at either the para or ortho position of the formyl group, such as p ‐anisaldehyde, o ‐anisaldehyde, p ‐tolualdehyde, 4‐hydroxybenzaldehyde, 2‐hydroxybenzaldehyde and thiophene‐2‐carbaldehyde, the reaction all exclusively led to the transformylation product 2 (Table 2). Among all the aryl aldehydes examined, p ‐anisaldehyde afforded the highest yield of 2 [15] . In the cases where the transformylation products were obtained in low yields, the unreacted amides were recovered.…”
Section: Resultsmentioning
confidence: 99%
“…When an aryl aldehyde bears an electron‐donating group at either the para or ortho position of the formyl group, such as p ‐anisaldehyde, o ‐anisaldehyde, p ‐tolualdehyde, 4‐hydroxybenzaldehyde, 2‐hydroxybenzaldehyde and thiophene‐2‐carbaldehyde, the reaction all exclusively led to the transformylation product 2 (Table 2). Among all the aryl aldehydes examined, p ‐anisaldehyde afforded the highest yield of 2 [15] . In the cases where the transformylation products were obtained in low yields, the unreacted amides were recovered.…”
Section: Resultsmentioning
confidence: 99%
“…Liu and co‐workers reported another Rh(III)‐catalyzed intermolecular redox‐neutral C–H activation and annulation reaction of O ‐benzylhydroxylamines and alkynes to provide isocoumarin derivatives where the O−N bond of the hydroxylamine acted as an internal oxidant [Scheme , Eq. (1)] …”
Section: Recent Advances In Isocoumarin Synthesismentioning
confidence: 99%
“…In 2013, Li et al demonstrated that copper(II) chloride could be used as both a chlorine source and a catalyst for the chloroamination of benzylated aminoalkenes. [16] A year later, the same research group developed a metal-free method using (diacetoxyiodo)benzene as a catalyst in the presence of pyridinium chloride. [17] An alternative method to synthesize 2chloromethylpyrrolidines involves the generation of an amidyl radical from N-chloroamines, [18] which could be subjected to cyclization in the presence of copper, [19] or titanium-based catalysts.…”
Section: Introductionmentioning
confidence: 99%